1996
DOI: 10.1021/bi952182t
|View full text |Cite
|
Sign up to set email alerts
|

Human pro-Tumor Necrosis Factor Is a Homotrimer

Abstract: The structure of human transmembrane pro-TNF-alpha was studied both in intact cell systems and in an in vitro translation system. In intact cell systems (LPS-induced THP-1 and TNF cDNA-transfected COS-7), a trimer of pro-TNF was detected after chemical cross-linking based on its molecular weight in Western blotting analysis. The trimer was shown to be a TNF-specific protein and could be partially cleaved to 26-kDa pro-TNF monomers by cleaving the cross-linkers. The trimeric structure was assembled intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
7

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 30 publications
1
82
0
7
Order By: Relevance
“…TRAF2 has therefore a dual role in TNF-induced ASK1 activation, firstly as an inducer of Trx-ASK1 dissociation by ROS induction and secondly, as an activating oligomerization scaffold for ASK1. In agreement with the existence of parallel TRAF2-dependent, JNK-activating pathways (TRAF2-GCKs-MEKK1 versus TRAF2-ROS-ASK1), it has been found that Trx-(SH) 2 completely blocks TRAF2-ASK1 interaction, but has only a partial inhibitory effect on TRAF2-mediated JNK activation. 159 TNF not only robustly activates the JNK-inducing MAP kinase cascade, but also the p38-MAPK signalling cascade.…”
Section: Ap-1supporting
confidence: 63%
See 1 more Smart Citation
“…TRAF2 has therefore a dual role in TNF-induced ASK1 activation, firstly as an inducer of Trx-ASK1 dissociation by ROS induction and secondly, as an activating oligomerization scaffold for ASK1. In agreement with the existence of parallel TRAF2-dependent, JNK-activating pathways (TRAF2-GCKs-MEKK1 versus TRAF2-ROS-ASK1), it has been found that Trx-(SH) 2 completely blocks TRAF2-ASK1 interaction, but has only a partial inhibitory effect on TRAF2-mediated JNK activation. 159 TNF not only robustly activates the JNK-inducing MAP kinase cascade, but also the p38-MAPK signalling cascade.…”
Section: Ap-1supporting
confidence: 63%
“…1,2 From this membrane-integrated form the soluble homotrimeric cytokine (sTNF) is released via proteolytic cleavage by the metalloprotease TNF alpha converting enzyme (TACE). 3 The soluble 51 kDa trimeric sTNF tends to dissociate at concentrations below the nanomolar range, thereby losing its bioactivity.…”
Section: General Aspects Of Tnf Biologymentioning
confidence: 99%
“…There are two forms of hTNF-α, a 26 kDa pro-TNF-α (the precursor of mature TNF-α) and a 17 kDa mature TNF-α [8,16,18]. Pro-TNF-α is a transmembrane protein with its N-terminus locating inside the cytoplasm and C-terminus outside of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Após clivagem por metaloproteases extracelulares entre os aminoácidos alanina76 e valina77 (BLACK et al, 1997) a forma madura solúvel de 157 aa (~17 kDa) é secretada, sendo monomérica e biologicamente inativa (TANG; HUNG; KLOSTERGAARD, 1996). A forma ativa compreende um homotrímero composto pelos monômeros de 17 kDa, embora haja envolvimento do TNFα transmembrânico na resposta inflamatória, igualmente existente como homotrímero formado por monômeros não clivados de 26 kDa (PEREZ et al, 1990;TANG;HUNG;KLOSTERGAARD, 1996).…”
Section: Caracterização Funcional Do Tnfα No Organismounclassified
“…A forma ativa compreende um homotrímero composto pelos monômeros de 17 kDa, embora haja envolvimento do TNFα transmembrânico na resposta inflamatória, igualmente existente como homotrímero formado por monômeros não clivados de 26 kDa (PEREZ et al, 1990;TANG;HUNG;KLOSTERGAARD, 1996). Descrita por Carswell e colaboradores, 1975, em experimentos de regressão e "necrose" de sarcomas, a presença do TNFα foi demonstrada em soro murino após infecção experimental com bacillus Calmette-Guérin (BCG) sensibilizado com endotoxina (CARSWELL et al, 1975).…”
Section: Caracterização Funcional Do Tnfα No Organismounclassified